2004
DOI: 10.1007/s00108-004-1273-9
|View full text |Cite
|
Sign up to set email alerts
|

Rechter Ventrikel bei arterieller Hypertonie

Abstract: Left ventricular hypertrophy is the best known and most evident cardiac organ manifestation of arterial hypertension. However, only limited findings are available on function and structure of the right ventricle. The published studies show that the right ventricle is also affected in the course of hypertensive heart disease. Particularly hypertrophy of the right ventricular free wall, impaired right ventricular diastolic filling, elevated right ventricular filling pressure as well as impairment of right ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…28 However, our study showed that subjects with MS who were free of arterial hypertension and diabetes also had higher prevalence of LV, RV, and biventricular hypertrophy which confirmed the theory that various humoral factors (circulating cytokines and growth hormones) such as angiotensin II, aldosterone, catecholamines, and insulin on both ventricles. 29 The LV structure has a great, perhaps the most significant influence on the RV structure and function, which was confirmed in our study. The analysis of our results showed that the LVMI and RWT were independently associated with the RV wall hypertrophy, which is consistent with the findings from the literature.…”
Section: Discussionsupporting
confidence: 87%
“…28 However, our study showed that subjects with MS who were free of arterial hypertension and diabetes also had higher prevalence of LV, RV, and biventricular hypertrophy which confirmed the theory that various humoral factors (circulating cytokines and growth hormones) such as angiotensin II, aldosterone, catecholamines, and insulin on both ventricles. 29 The LV structure has a great, perhaps the most significant influence on the RV structure and function, which was confirmed in our study. The analysis of our results showed that the LVMI and RWT were independently associated with the RV wall hypertrophy, which is consistent with the findings from the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Briefly, the following mechanisms can be hypothesized: (1) the increased LV filling pressure is translated to the pulmonary circulation, (2) a mechanical interaction occurs between the RV and LV and (3) both ventricles are exposed to humoral stimuli, namely circulating cytokines and growth hormones, such as angiotensin II, aldosterone, catecholamines and insulin. 28 To this purpose, it should be pointed out that our subjects with and without MS were similar for age, known duration of hypertension, as well as SBP and DBP; this supports the view that the prevalence and degree of biventricular involvement was not related to the differences in pressure load or in demographic and clinical variables known to affect cardiovascular structure, but rather to synergic influence of metabolic abnormalities characterizing MS. The difference in RV involvement described in the present study is smaller than previously reported, probably due to the fact that in previous studies hypertensive and normotensive individuals or subjects with and without LVH were compared.…”
Section: -Test (For Categorical Variables)supporting
confidence: 76%
“…3 Which leads to left ventricular hypertrophy, [3][4][5] CHF, cardiac arrhythmias, diastolic dysfunction and abnormalities of blood flow due to atherosclerotic coronary artery disease and microvascular disease.…”
Section: Introductionmentioning
confidence: 99%